Active and Passive Vibration Control of Structures - Hagedorn, Peter; Spelsberg-Korspeter, Gottfried (CISM International Centre for Mechanical Sciences, 2014)
Active and Passive Vibration Control of Structures form an issue of very actual interest in many different fields of engineering, for example in the automotive and aerospace industry, in precision engineering (e.g. in large telescopes), and also in civil engineering. The papers in this volume bring together engineers of different background, and it fill gaps between structural mechanics, vibrations and modern control theory.Â Â Also links between the different applications in structural control are shown.